CHOICE OF ANTIBIOTIC IN THE TREATMENT OF COMMUNITY-ACCOMBINED PNEUMONIA IN CHILDREN IN HOSPITAL CONDITIONS - Щербатюк, Наталія (SWorldJournal, 2022)
Background. Currently, the difficulty with the choice of antimicrobial drugs arises in the treatment pneumonia in the hospital. The misuse of antibiotics is one of the reasons for the rapid growth of antibiotic resistance. The article provides data on pre